The Effect of Work-Life Balance on Employee Performance Mediated by Job Satisfaction at Bela International Hotel Ternate - Risaldi M. Saleh; Fadhliah M Alhadar; Ruslan A Kamis (Dinasti Publisher, 2025)
The objectives of this study are: (1) To test whether work-life balance affects employee performance at Bela Internatinonal Hotel Ternate; (2) To test whether work-life balance has an effect on job satisfaction at Bela International Hotel Ternate; and (3) to test whether job satisfaction affects employee performance at Bela International Hotel Ternate; (4) To test whether work-life balance has an effect on employee performance mediated by job satisfaction at Bela International Hotel Ternate. The number of research samples was 108 employees of Bela International Hotel Ternate. The test tool used is stuctural equation modeling (SEM) using the smart partial least square (PLS) statistical program as a statistical test tool. The results of the study show that: (1) Work-Life Balance has a positive and significant effect on employee performance at Bela International Hotel Ternate. The results of this study mean that employees with a good work-life balance will have a balance in personal and work matters; (2) Work-Life Balance has a positive and significant effect on job satisfaction at Bela International Hotel Ternate. The results of this study mean that, the higher employee job satisfaction, the more employee performance increases; (3) Job Satisfaction has a positive and significant effect on employee performance at Bela International Hotel Terante; (4) Work-Life Balance has a positive and significant effect on employee performance through job satisfaction as a mediating variable at Bela International Hotel Ternate.